2010
DOI: 10.1007/s00247-010-1834-0
|View full text |Cite
|
Sign up to set email alerts
|

Nasogastric tubes and videofluoroscopic swallowing studies in children

Abstract: The presence of a nasogastric tube does not alter the findings of VFSS; however, it might increase the incidence of respiratory compromise when aspiration is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Although healthy adults can adapt their swallow function to accommodate NG tubes [12] children with dysphagia may have impaired ability to do this. Previous authors [2][3] have suggested that individuals with dysphagia may not be able to compensate as well for tube placement by sustaining the upper esophageal sphincter opening longer than normal. This could lead to increased pharyngeal residue, particularly in the pyriform sinuses, which may then aspirate into the airway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although healthy adults can adapt their swallow function to accommodate NG tubes [12] children with dysphagia may have impaired ability to do this. Previous authors [2][3] have suggested that individuals with dysphagia may not be able to compensate as well for tube placement by sustaining the upper esophageal sphincter opening longer than normal. This could lead to increased pharyngeal residue, particularly in the pyriform sinuses, which may then aspirate into the airway.…”
Section: Discussionmentioning
confidence: 99%
“…However, literature supporting this practice in the pediatric population is sparse. There has been one pediatric study evaluating patients with and without NG tubes, using the patient as their own control, which concluded that there was no significant difference in VFSS findings with and without an NG tube in place [3]. The authors do not specify if the NG tube was in place with the first or second VFSS and noted that the interval between the two studies ranged from 2 weeks to 18 months, with a mode of 3 months [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides being important for explaining the presence of aspiration or micro aspiration 1 , the study of swallowing using a radiological technique (Videodeglutogram or Videofluoroscopy of Swallowing) optimizes the identification of the safest way to feed a patient with dysphagia. The maintaining a safe dose of radiation 16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the causes of dysphagia in pediatric populations are often somewhat different than in adult patients [5]. Table 3 summarizes common causes of dysphagia in pediatric patients [1,5,6,7,8,9,10,11,12,13]. …”
Section: Common Causes Of Dysphagiamentioning
confidence: 99%